Clinical Feasibility of Completely Autologous Fibrin Glue in Spine Surgery - Yuki Taniguchi; Yoshitaka Matsubayashi; Toshiyuki Ikeda; So Kato; Toru Doi; Yasushi Oshima; Hitoshi Okazaki; Sakae Tanaka (Spine Surgery and Related Research, 2022)
Introduction: Fibrin glue is widely used in spine surgery. Nevertheless, no report has demonstrated the feasibility of completely autologous fibrin glue (CAFG) in spine surgery. This study aims to investigate the safety, efficacy, and effect of bone fusion of CAFG on spine surgery. Methods: We retrospectively extracted data of patients who underwent primary spine surgery with preoperatively prepared CAFG. Primary outcomes were the incidence of wound-related unplanned reoperations within 90 days following primary surgery and the occurrence of reoperation for the management of cerebrospinal fluid (CSF) leakage in patients who had been treated with CAFG used as dural sealants. The effect of CAFG on bone fusion was also assessed by detecting implant failure at one year postoperatively in patients aged 25 years or less undergoing primary fusion for idiopathic scoliosis. Results: We identified 131 eligible patients (47 males and 84 females) with a mean age of 32.3 years. CAFG was used most frequently as an adhesive for fixation of graft bone (110 patients), followed by as a dural sealant for CSF leakage in 17 patients, and as a local hemostatic agent in four patients. Wound-related reoperations were identified in four patients (3.1%), which included three for surgical site infection, and one for postoperative epidural hematoma. There was no reoperation required for the management of CSF leakage among 17 patients with dural incision or incidental durotomy. Compared with the control cohort, the use of CAFG was not associated with early wound-related reoperations or implant failure in patients with spinal deformity. Conclusions: We demonstrated the clinical feasibility of CAFG in spine surgery. The use of CAFG was not associated with the incidence of reoperations for wound-related complications. CAFG worked effectively as a dural sealant for preventing CSF leakage. CAFG had no beneficial or adverse effect on spinal bone fusion.